Growth and mortality of sympatric Atlantic salmon and brown trout fry in fluctuating and stable flows - Addo, Louis; Hajiesmaeili, Mahboobeh; Piccolo, John; Watz, Johan (Ecology of Freshwater Fish, 2023)
Sub-daily fluctuations in streamflow may have adverse effects on the biota downstream of dams in hydropeaking-regulated rivers. Although the stranding of salmonid fry is one documented effect of hydropeaking, little is known about the species-specific behavioural and subsequent growth effects of sub-daily flow fluctuations. We investigated the effects of sub-daily flow fluctuation on growth, mortality and behaviour of sympatric Atlantic salmon (Salmo salar) and brown trout (S. trutta) fry (29–34 mm) in a laboratory experiment. The fluctuating flow treatment negatively affected growth and increased mortality for trout but not for salmon. The level of aggressive behaviour was similar in the fluctuating- and stable-flow treatments. Within the fluctuating flow treatment, there was a trend that more fishes were visibly active above the substrate during low than high flow. These findings suggest that hydropeaking-induced flow fluctuations may affect fry of different salmonid species in different ways and that brown trout fry may be more vulnerable to hydropeaking effects than Atlantic salmon fry. It can therefore be important to consider the possibility of divergent reactions by different fish species under hydropeaking situations and to incorporate species-specific strategies to conserve culturally and economically relevant riverine fish species.